FIRST AND SECOND TRIMESTER MEDICAL ABORTION - PILOT STUDY IN REPUBLIC OF NORTH MACEDONIA - Georgievska, Jadranka; Tofoski, Gligor; Daneva Markova, Ana; Zafirova Ivanovska, Beti; Jovanovska, Viktorija; Petrovski, Ljupcho; Stefanija, Adela; Kjaev, Ivo; Bina, Arta; Dimitrovski, Sasho; Buklioska, Adriana; Sozovska Belchovska, Eva; et al. (Македонско лекарско друштво = Macedonian medical association, 2021)
Introduction. Medical abortion is a procedure in which medication is used to end a pregnancy up to 22 weeks of gestation. The aim of this study was to assess the efficiency, safety and acceptance of medical abortion in the first and second trimester using a regimen of medications, mifepristone followed by misoprostol. Methods. In a prospective study, conducted at the University Clinic for Gynecology and Obstetrics in Skopje in the period from March to November 2021, women that came for medical abortion in the first and second trimester were enrolled. They were divided into two groups: Group I (5 to 12 weeks of gestation) and Group II (12 to 22 weeks of gestation). Participants in Group I were given 200 mg mifepristonе for peroral application and after 24 hours instructed for sublingual application of 800 µg misoprostol at home. Participants in Group II were hospitalized and treated with the same regimen. Additional dosage of misoprostol was given to complete abortion. Results. A total of 208 women with medical abortion up to 22 weeks of gestation (173 in the first group and 35 in the second group) were enrolled in the study. In the first group a complete uterine evacuation was achieved in 168 women (97.1%) and in 25 women (71.4%) in the second group. Acceptability of the method was high among both groups (95.14 % in Group I and 82.14 % in Group II). All doctors/clinicians who participated in this pilot study were satisfied with the method. Conclusions. Medical abortion is effective, safe and acceptable option for women in the first and second trimester. Acceptability of the method was high among both groups. All doctors/clinicians who participated in this pilot study were satisfied with the method and would offer it as an option to their patients in the future.
МЕДИКАМЕНТОЗЕН АБОРТУС ВО ПРВ И ВТОР ТРИМЕСТЕР - ПИЛОТ СТУДИЈА ВО РЕПУБЛИКА СЕВЕРНА МАКЕДОНИЈА
Keywords: medical abortion; efficacy; acceptance; first and second trimester